1.5(2x-4)=.5(x+3)-4

Simple and best practice solution for 1.5(2x-4)=.5(x+3)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.5(2x-4)=.5(x+3)-4 equation:


Simplifying
1.5(2x + -4) = 0.5(x + 3) + -4

Reorder the terms:
1.5(-4 + 2x) = 0.5(x + 3) + -4
(-4 * 1.5 + 2x * 1.5) = 0.5(x + 3) + -4
(-6 + 3x) = 0.5(x + 3) + -4

Reorder the terms:
-6 + 3x = 0.5(3 + x) + -4
-6 + 3x = (3 * 0.5 + x * 0.5) + -4
-6 + 3x = (1.5 + 0.5x) + -4

Reorder the terms:
-6 + 3x = 1.5 + -4 + 0.5x

Combine like terms: 1.5 + -4 = -2.5
-6 + 3x = -2.5 + 0.5x

Solving
-6 + 3x = -2.5 + 0.5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.5x' to each side of the equation.
-6 + 3x + -0.5x = -2.5 + 0.5x + -0.5x

Combine like terms: 3x + -0.5x = 2.5x
-6 + 2.5x = -2.5 + 0.5x + -0.5x

Combine like terms: 0.5x + -0.5x = 0.0
-6 + 2.5x = -2.5 + 0.0
-6 + 2.5x = -2.5

Add '6' to each side of the equation.
-6 + 6 + 2.5x = -2.5 + 6

Combine like terms: -6 + 6 = 0
0 + 2.5x = -2.5 + 6
2.5x = -2.5 + 6

Combine like terms: -2.5 + 6 = 3.5
2.5x = 3.5

Divide each side by '2.5'.
x = 1.4

Simplifying
x = 1.4

See similar equations:

| A=45 | | 5(3a-7)-9=46 | | 2.15x-4.63=x+1.19 | | 4x(x)(x)-25x=0 | | 5-2(x+3)+2= | | 4(2a-6)-8=46 | | 3(2y+6)=12 | | (5y-6)=7(2-4y) | | (4x)(4x)(4x)-25x=0 | | 2+5x-x^2= | | 19.55=8.5 | | 7(5y-6)=2-4y | | 3x-6=5x+15-4 | | x^2-x=132 | | (4x+9)-(5x-8)=11 | | .22(x+6)=.2x+4.7 | | 1.2(x-3)=10.8 | | 4x-(2x+4)= | | (x)(x)-9x+14=0 | | 8y=40-5x | | 7(4y-y+4)= | | 3x+18=4x+8 | | x^2+y^2+2x-4y-2=0 | | -(p+10)= | | -6(a+6)= | | 0.3x+1.5=8.4 | | (5x)4= | | (4h)5= | | 1000(8x-10)=40(1180+100x) | | 9-3y+15y^2=9 | | 7e^5x=10e^8x | | 9y-2z-12y+7z= |

Equations solver categories